Planes, trains, and all the feels - Hart, Livy (Amara, an imprint of Entangled Publishing LLC, 2023)
As the black sheep of the family, choreographer Cassidy Bliss vowed she'd do anything to get home in time to help with her sister's wedding and avoid family disappointment...again. She just never expected "anything" would involve sharing the last rental car with the jerk who cut her off in line at the airport this morning. But horrible times apparently call for here-goes-nothing measures. Driving across the country with Luke "life can be solved with a spreadsheet" Carlisle must be a penance for some crime she committed. Because the second he opens his mouth, it's all she can do to not maim him with her carry-on. But somewhere between his surprisingly thoughtful snack sharing and his uncanny ability to see straight to the core of her, her feelings go unchecked. Suddenly, their crackling chemistry is just one more thing they have to navigate--and it couldn't come at a worse time. But after a lifetime of letting the expectations and needs of others drive her life, Cassidy must decide if she's ready to take the wheel once and for all.